Percepción ambiental del poblador sobre los residuos sólidos domiciliarios generados en el asentamiento humano Ollanta Humala, distrito de San Juan Bautista, Loreto - Perú, 2022 - Claudio Faijo, Lucia Susana (2022)
The present work of thesis was developed in the Ollanta Humala Human Settlement situated at the 1.5 km on the right side of the highway Santo Tomas, the evaluation was realized during the months of February to June 2022, and it had had as objective evaluated the perception of the rural villager of the Ollanta Humala Human Settlement and its relation with the environmental problematic of the municipal solid waste, also, characterizer to the population in study into the aspects of knowledge; with the propose of to know about the environmental problematic of the solid waste in its environment. Therefore, the present work of thesis pretends generate information from the perception of the rural villager about the municipal solid waste in the Ollanta Humala Human Settlement, through the application of a survey format which covers the aspects of knowledge, awareness and management of municipal solid waste, and propose a proposal for better management, segregation and disposal, with the aim of making residents aware of the environmental problematic that represented the generation of household solid waste.